An LC-MS/MS method for the simultaneous determination of 18 antibacterial drugs in human plasma and its application in therapeutic drug monitoring - Lu, Wei; Pan, Meng; Ke, Hongqin; Liang, Jun; Liang, Wenbin; Yu, Ping; Zhang, Penghua; Wang, Qibin (Frontiers in Pharmacology, 2022)
Antimicrobial resistance (AMR) is a major threat to global health due to the wide use of antibacterial drugs. Multiple studies show that the pharmacokinetic /pharmacodynamic (PK/PD) studies of antibiotics are an approach to prevent/delay AMR. The pharmacokinetic parameters of antibiotics are the basis of PK/PD studies, and therapeutic drug monitoring (TDM) is the key method to obtain pharmacokinetic information. We developed an ultra-performance liquid chromatography–tandem mass spectrometry to determine 18 antibacterial drugs (piperacillin, cefazolin, cefuroxime, cefoperazone, ceftriaxone, cefepime, aztreonam, meropenem, imipenem, levofloxacin, moxifloxacin, azithromycin, clindamycin, tigecycline, linezolid, vancomycin, voriconazole and caspofungin) in human plasma for practical clinical usage. Samples were prepared using protein precipitation with methanol. Chromatographic separation was accomplished in 6 min on a BEH C18 column (2.1 × 100 mm, 1.7 µm) using a gradient elution of acetonitrile and 0.1% formic acid in water at a flow rate of 0.3 mL/min. The electrospray ionization source interface was operated in the positive and negative ionization modes. Inter- and intra-day precision, accuracy, recovery, matrix effect, and stability were validated according to the Food and Drug Administration guidance. The correlation coefficients of calibration curves were all greater than 0.99. The accuracies of the 18 antibacterial drugs ranged from 89.1% to 112.4%. The intra-day precision of the analytes ranged from 1.4% to 9.3% and the inter-day precision from 2.1% to 7.2%. The matrix effects ranged from 93.1% to 105.8% and the extraction recoveries ranged between 90.1% and 109.2%. The stabilities of the 18 antibacterial drugs in plasma were evaluated by analyzing three different concentrations following storage at three storage conditions. All samples displayed variations less than 15.0%. The validated method was successfully applied to routine clinical TDM for 231 samples.